2021
DOI: 10.2147/jep.s305936
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and in-vitro Evaluation of Antibacterial Activities of Echinops amplexicaulis, Ruta chalepensis and Salix subserrata Against Selected Pathogenic Bacterial Strains in West Shewa Zone, Ethiopia

Abstract: Background: Although traditional healers in Ethiopia have a long history of using medicinal plants to treat diseases in animals and humans, studies on the antibacterial activities and potential bioactive ingredients of most medicinal plants have been insufficient. Therefore, this study aimed to evaluate the in-vitro antibacterial activities and to screen phytochemical constituents of selected medicinal plants against reference bacterial strains. Methods: The fresh and healthy roots of Echinops amplexicaulis, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Phytochemical tests for flavonoids, saponins, lactones, phenolic hydroxyls, unsaturation, coumarins, alkaloids, sesquiterpene lactones, steroids, terpenes, carbonyl groups, sugars, and anthocyanins were performed on both plant material and C. citratus EO using previously reported methodologies [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Phytochemical tests for flavonoids, saponins, lactones, phenolic hydroxyls, unsaturation, coumarins, alkaloids, sesquiterpene lactones, steroids, terpenes, carbonyl groups, sugars, and anthocyanins were performed on both plant material and C. citratus EO using previously reported methodologies [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that the extraction of chloroform, ethyl acetate, and butanol isolated four compounds, namely, 7-hydroxy-6-methoxycoumarin, Kaempferol, Quercetin and quercetin 3-O-a-L-rhamno glucopyranosyl (Rutin), and revealed the presence of phytochemicals, carbohydrates and/or glycosides, avonoids, sterols and/or triterpenes, alkaloids, protein and/or amino acids, Resins, Lactones and/or esters, and tannins(18). Another study reported that alkaloids, tannins, saponins, avonoids, and phytosterols and subjected to antibacterial activities of R. chalepensis (Fruit) against S. aureus, P. aeruginosa, E. coli, and S. pneumoniae (19). Another study also reported that Total phenol contents and avonoid contents were 6.22 mgGAE/g and 6.59 mg QE/g respectively and revealed the presence of hesperidin (591.9 mg/g dry extract) and rutin (266.7 mg/g dry extract), antioxidant activities of DPPH scavenging (IC 50 ) 60 µg/mL and lipid peroxidation (IC 50 ) value of 16.9 µg/mL.…”
Section: Introductionmentioning
confidence: 99%